2016
DOI: 10.1038/ijo.2016.226
|View full text |Cite
|
Sign up to set email alerts
|

Body fat evolution as predictor of retinal microvasculature in children

Abstract: Our analysis over a 7-year period shows that changes in body fat during childhood are already associated with the CRVE (especially in boys).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…from 30 weeks of gestation to 18 years. We found 23 studies reporting on measures of weight status (88%) as exposure, 23,28,38,39,[55][56][57][58][59][60][61][62][63][64][65][68][69][70][71][72][73][74][75] while measures of PA were present in six studies (23%) 41,64-67, 73 and SB was assessed in three studies (12%) 28,41,73 ; four studies (15%) reported measures of weight status and PA/SB. 28,64,65,73 Adiposity assessments included birthweight (n = 5), BMI (n = 11), OCT device, non-mydriatic vessel analyzer and a spectralis OCT device (4% each).…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 97%
See 4 more Smart Citations
“…from 30 weeks of gestation to 18 years. We found 23 studies reporting on measures of weight status (88%) as exposure, 23,28,38,39,[55][56][57][58][59][60][61][62][63][64][65][68][69][70][71][72][73][74][75] while measures of PA were present in six studies (23%) 41,64-67, 73 and SB was assessed in three studies (12%) 28,41,73 ; four studies (15%) reported measures of weight status and PA/SB. 28,64,65,73 Adiposity assessments included birthweight (n = 5), BMI (n = 11), OCT device, non-mydriatic vessel analyzer and a spectralis OCT device (4% each).…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 97%
“…The exposures were birthweight, 63 BMI 60,74,75 and WC. 75 No associations were found between WC z-scores and retinal arterioles, venules and AVR. 75 We found two studies using a clustered randomised controlled trial design in which exposures included weight 64 and PA. 64,66 No differences between intervention and control groups were found for weight and retinal parameters at the end of the intervention, whereas for PA results showed improvements in vascular parameters.…”
Section: Longitudinal Associationsmentioning
confidence: 99%
See 3 more Smart Citations